A Therapeutic Trial of Valganciclovir in Patients with Uveitis and Positive Epstein-Barr virus Early Antigen D IgG Titers. Issue 1 (January 2016) - Boonsopon, Sutasinee; Maghsoudlou, Armin; Kombo, Ninani E.; Foster, C. Stephen
Purpose: To evaluate the effectiveness of a therapeutic trial of valganciclovir in patients with uveitis with positive Epstein-Barr virus early antigen D immunoglobulin G titers (EBV EA-D). Methods: We performed a retrospective chart review of 14 patients at the Massachusetts Eye Research and Surgery Institution who had uveitis with positive EBV EA-D but negative studies for all other causes of uveitis and were treated with valganciclovir 450 mg twice a day or valganciclovir 900 mg twice a day between January 2010 and August 2014. Results: Nine of 14 patients, who had presumed EBV reactivation with associated intraocular inflammation, were successfully treated with valganciclovir: 3 of these were treated with valganciclovir 450 mg twice a day and 6 were treated with valganciclovir 900 mg twice a day. Five of 14 patients failed to respond to valganciclovir with persistent inflammation after at least 2 weeks of valganciclovir therapy, and were subsequently treated with immunomodulatory therapy to control inflammation. Conclusions: Uveitis can be caused by EBV infection/reactivation. A therapeutic trial with valganciclovir 450 mg twice a day for 1 month in patients with uveitis with positive EBV EA antibody may be beneficial.